Gender, Feminism, and Queer Theory in the Self-Study of Teacher Education Practices
XII, 174 p.
Keywords: This edited volume gives explicit attention to the influence of gender, feminism, and queer theory in self-study of teacher education practices. It builds on the self-study community’s interest in social justice that has mostly been focused on race, ethnicity, gender, disability, and power, as well as broad conceptions that include multiculturalism and ways of knowing. This is the time to examine gender both because our community is growing and because of the reconceptualization of issues of gender, feminism, and queer theory in teacher education. This collection of papers provides a space for members of the self-study field, from founders to welcomed new members, along with the general community of teacher educators to problematize these issues through a variety of theoretical lenses. As always with self-study the impetus of the research is on the improvement of individual practice. Readers will find innovative approaches and insights into their own work as teacher educators.